1994
DOI: 10.1007/bf00120341
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of hydrogels of poly(vinyl alcohol) and hyaluronic acid

Abstract: Hydrogels of hyaluronic acid (HA) and poly(vinyl alcohol) (PVA) were prepared using eight freezing-thawing cycles from HA/PVA blends (10/90, 20/80, 30/70, 40/60, 50/50, and 0/100 (w/w) ratios). The biocompatibility of the hydrogels was tested by means ofin vitro cytotoxicity and cytocompatibility tests using cell culture techniques. The release with time of HA and PVA, the two hydrogel components, ion aqueous medium was also monitored and evaluated. The results indicate that all the hydrogels are not cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Cell culture experiments have demonstrated that, without coagulation, hydrogels with one freeze‐thaw cycle were not stable enough to sustain cell culture, because fast degradation compromises the pH of the culture medium. Low cell adhesion was reported before for composite hydrogels without coagulation treatment,38 which might be attributed to this fact. PVA hydrogels themselves demonstrated very low cell attachment and only a few cells were observed after 10 days of culture, which further demonstrated the necessity of inclusion of substitutes.…”
Section: Discussionmentioning
confidence: 83%
“…Cell culture experiments have demonstrated that, without coagulation, hydrogels with one freeze‐thaw cycle were not stable enough to sustain cell culture, because fast degradation compromises the pH of the culture medium. Low cell adhesion was reported before for composite hydrogels without coagulation treatment,38 which might be attributed to this fact. PVA hydrogels themselves demonstrated very low cell attachment and only a few cells were observed after 10 days of culture, which further demonstrated the necessity of inclusion of substitutes.…”
Section: Discussionmentioning
confidence: 83%
“…2. 2000 term in vivo animal studies and in vitro cell culture studies (23,24). However, further studies would have to be conducted to prove the biocompatibility of PVA in the cochlea as well as in soft tissue before clinical use with cochlear implants.…”
Section: Discussionmentioning
confidence: 99%
“…To limit the diffusion of the product so that it remained in the immediate vicinity of the bound enzyme on the array, we applied the enzyme substrate in a thin coating of PVA. PVA is nonfluorescent, optically transparent, water-soluble, and highly viscous and has applications in many biological assays. , The diffusion coefficient of fluorescein in a layer of 5% PVA in phosphate buffer was measured via fluorescence recovery after photobleaching (FRAP) and found to be ∼50 μm 2 /s, roughly 6-fold slower than in phosphate buffer without PVA (Supporting Information Figure S1). As shown in Figure d, it was relatively easy to resolve the enzyme activity in the spots with little cross contamination.…”
Section: Resultsmentioning
confidence: 99%